Flat mites (Tenuipalpidae) from Bahia state, Northeastern Brazil- a checklist including new records and an illustrated key to species - Nascimento, Renata S.; Souza, Kaelem S.; Melo, Elisangela A. S. F.; Tassi, Aline D.; Castro, Elizeu B. [UNESP]; Navia, Denise; Mendonca, Renata S. de; Ochoa, Ronald; Oliveira, Anibal R. (Acarologia-universite Paul Valery, 2023)
Tenuipalpidae (Trombidiformes: Tetranychoidea) is an economically important family of plant-feeding mites. The family has approximately 1,100 described species in 41 genera with worldwide distribution. Currently, 40 species of Tenuipalpidae have been recorded from Brazil, and prior to this study only 11 were known from Bahia state. Five new species records are presented here for Bahia, making a total of 16 species now known from the state. Brevipalpus is considered the most important genus due to their association with, and ability to transmit, devastating plant viruses. Some diseases caused by viruses transmitted by Brevipalpus mites (VTBs) have already been recorded in the state of Bahia, such as the Passion fruit green spot virus and citrus leprosis. This paper presents a checklist of tenuipalpids reported from the state of Bahia in Brazil, including new records and an illustrated identification key to the species.
Keywords: taxonomy; false spider mites; diversity; Brevipalpus; diagnostics; plant viruses